1997
DOI: 10.1152/jn.1997.78.4.2217
|View full text |Cite
|
Sign up to set email alerts
|

GABAA-Mediated Local Synaptic Pathways Connect Neurons in the Rat Suprachiasmatic Nucleus

Abstract: The suprachiasmatic nucleus (SCN) in mammals functions as the biological clock controlling circadian rhythms, but the synaptic circuitry of the SCN is largely unexplored. Most SCN neurons use the neurotransmitter gamma-aminobutyric acid (GABA), and anatomic studies indicate many GABAergic synapses and local axon collaterals; however, physiological evidence for synaptic communication among SCN neurons is indirect. We have used three approaches to investigate local circuitry in the SCN in acute hypothalamic slic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 15 publications
3
62
0
Order By: Relevance
“…Most SCN neurons receive robust local inhibitory input (19). We examined spontaneous IPSCs in PRV-EGFP-labeled SCN neurons to determine if inhibition was also intact in these cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most SCN neurons receive robust local inhibitory input (19). We examined spontaneous IPSCs in PRV-EGFP-labeled SCN neurons to determine if inhibition was also intact in these cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SCN neurons receive a tonic GABA A receptor-mediated synaptic input that, at least partly, originates within the SCN itself and peaks during the night (Kim and Dudek, 1992;Jiang et al, 1997;Strecker et al, 1997;Itri et al, 2004). Early work suggested that GABA could evoke excitatory responses during the day (Wagner et al, 1997), but the generality of this finding has been questioned by other laboratories (Gribkoff et al, 1999;De Jeu and Pennartz, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This technique selectively depolarizes soma and dendrites, but not axons. Glutamate photostimulation involves focal release of glutamate using ultraviolet light projected into the slice [6,11,19,29,36]. This method of stimulation avoids physical contact with the slice and affords the advantage of being able to stimulate neurons at multiple, discrete sites within the slice.…”
Section: Introductionmentioning
confidence: 99%